Pengaruh Eleksibilitas Kerja, Kepemimpinan Digital dan Work Life Balance Terhadap Komitmen Karyawan dengan Kesejahteraan Mental Sebagai Variabel Intervening pada Bank BTN KC Bangkalan - Asis Riyanto; Careen Adhania Kautsar; Siti Mujanah; Achmad Yanu Alif Fianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyse the influence of work flexibility, digital leadership, and work-life balance on employee commitment, with mental well-being as a mediating variable. This study was conducted on BTN Bank employees in KC Bangkalan Regency using a quantitative approach. Data was collected through questionnaires from 50 respondents and analysed using regression tests and Sobel Test to test the mediation effect. The results showed that work flexibility, digital leadership, and work-life balance have a positive and significant influence on mental well-being. In addition, mental well-being has a significant influence on employee commitment and mediates the relationship between the three independent variables and employee commitment. Digital leadership provides the largest mediating effect compared to work flexibility and work-life balance, confirming the importance of the leader's role in supporting employees' mental well-being in the era of digital transformation. The findings imply that Bank BTN can improve employee commitment by implementing work flexibility policies, supporting work-life balance, and strengthening digital leadership competencies. This research also contributes to the human resource management literature by offering a new perspective in supporting employees' mental well-being as a strategic factor in increasing organisational loyalty.